Pengaruh kompetensi, motivasi dan skeptisme profesional terhadap kualitas audit auditor inspektorat se-provinsi Riau - Afriyani, Neni; Anugerah, Rita; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research was to asses the influence of competence, motivation and professional skepticism towards on audit quality of inspectorate auditor in Riau province. Data for this study was obtained from samples of auditors who work in inspectorate in Riau Province. A total of 29 responses obtained and used in the analysis. Data was analized using smartPLS software. The results showed that (1) the competence and motivation do not have impact on audit quality, (2) but professional skepticism have a significant impact on audit quality.Key words: competence, motivation, professional skepticism and audit quality.